ANALISIS CLUSTERING MENGGUNAKAN ALGORITMA K-MEANS TERHADAP PENJUALAN PRODUK PADAPT BATAMAS NIAGA JAYA - Mesri Silalahi (Universitas Putera Batam, 2018)
PT Batamas Niaga Jaya was established in 1994 located in Sagulung Mas Indah complex, Sagulung Batu Aji district, Batam. This PT rents out 24 kiosks and 48 counters, in the retail sector, PT has 4 stores, namely BIG supermarket, Department store, Stationary and 7,500 convenience store and 10,000 department stores. 7,500 Convenience Stores and 10,000 Stores PT Batamas Niaga Jaya sells various products including food, beverages, kitchen utensils and equipment, and various daily necessities. Sales transactions for 7,500 convenience stores and 10,000 convenience stores were used as objects for analysis. PT Batamas Niaga Jaya often has problems in product management, the company is unable to classify the best-selling products and is not in demand, so it often lacks selling products and piles of non-salable products. The data used is sales data for the last 3 months (February 2018-April 2018). The data cluster technique uses the K-Means algorithm where the data are grouped into several clusters based on the similarity of the data. The results of the study obtained 2 product groups, namely products that were not in demand with the C0 group and the best-selling product group with the C1 group. The C0 product group that is not in demand consists of 657 products and the C1 group consists of 70 products which are in demand.